Vers la « Blue Society » - Philippe Vallette (VertigO)
Aware of the importance of tourism in coastal areas, conflicts of use, the deterioration of the coastal environment and the relatively small number of publications dealing with tourism stakeholders vis-à-vis the Integrated Coastal Zone Management (ICZM), we decided to conduct an exploratory study on the subject. Our study area is concentrated on the Atlantic coast, a coherent geographical area, due to the relatively similar characteristics of the regions studied. We interviewed the senior management in four coastal stations and local actors who we considered representative because directly involved in the implementation of ICZM. The aim of the Blue Society is to meet the society’s present and future needs in a spirit of “positive” growth, based on the huge potential the ocean offers us. It is based on the responsible use of marine resources, as well as the development of innovative technologies and new products generating employment and economic resources. Thanks to the exchange of know-how, to the sharing of knowledge and to the appropriation of that vision by scientists, companies, policy-makers and citizens, positive solutions and innovative experiences could emerge and be a part of the creation of a new sustainable and fair society.